A Wearable Capacitive Sensor Based on Ring/Disk‐Shaped Electrode and Porous Dielectric for Noncontact Healthcare Monitoring (Global Challenges 5/2020). Issue 5 (22nd April 2020) - Zheng, Ya‐Nan; Yu, Zhe; Mao, Guoyong; Li, Yunyao; Pravarthana, Dhanapal; Asghar, Waqas; Liu, Yiwei; Qu, Shaoxing; Shang, Jie; Li, Run‐Wei
Abstract : In article 1900079, Jie Shang, Run‐Wei Li, and co‐workers report a wearable capacitive sensor that can monitor human physiological signals (pulse and respiratory) in the non‐contact mode. This is achieved by using asymmetrical ring/disk‐shaped conductive material and low‐dielectric porous material to enhance the capacitive coupling effect.